Effect of loperamide and naloxone on gastric acid secretion in healthy man. Issue 9 (September 1981) - Caldara, R; Cambielli, M; Masci, E; Guslandi, M; Barbieri, C; Ferrari, C
Abstract : The effect of acute oral administration of three different doses (4, 8, and 16 mg) of loperamide, a peripheral opiate agonist, on basal and submaximal pentagastrin-stimulated gastric acid secretion was evaluated in healthy volunteers. Both basal and stimulated gastric secretion were significantly lowered by 8 and 16 mg of the drug in comparison with a control study, while 4 mg was ineffective. Naloxone, a specific opiate antagonist, decreased slightly but not significantly both basal and pentagastrin-stimulated gastric acid secretion, when infused intravenously at the rate of 30 micrograms/kg/h, but completely abolished the inhibitory effect of loperamide on gastric acidity. These data also suggest that opiates may be involved in the regulation of gastric acid secretion in man by acting at a peripheral site, as loperamide does not cross the blood-brain barrier.